Production Cycle Internal Control Audit - Pečiūrienė, Aleksandra; Pečiūra, Vilmantas (Ekonomika, 2002)
One effective way to perform an audit is to classify some similar transactions and accounts into so called cycles of related activities. A production cycle is rather special for manufacturing enterprises. This article describes the production cycle typical activities, elements of control structure, source documents. It emphasizes importance of control risk assessment to govern the nature, timing, and extent of substantive audit procedures that will be applied in the audit of account balances in the production cycle. In order to evaluate production cycle control risk, it is necessary to determine whether controls are in place and performed properly by company personnel. Auditors should: define the general control objectives in specific examples related to production; gather information about the production cycle control structure initially by completing an internal control questionnaire; perform detail test of controls audit procedures as part of an audit program for obtaining evidence useful in a final control risk assessment. The tests of controls procedures are designed to test the production accounting in two directions. One is the completeness direction, in which audit is focused on the recording of all the production that was started. The other direction is the validity direction, aimed to check proper recording of work in process and finished goods in the general ledger. If the control risk is assessed as low, the substantive audit procedures can be limited in cost-saving way, and analytical procedures can be used with more confidence. If tests of controls reveal weaknesses, the substantive procedures will need to be designed to lower the risk of failing to detect material errors in the production cycle accounts balances.